A határok és a határon átnyúló kapcsolatok átértékelődése Kelet-Közép-Európában - Süli-Zakar, István (Közép-Európai Közlemények, 2009)
On the basis of empirical research carried out in the border regions, euroregions and eurometropolises, elaboration of innovation oriented, cross-border economic development, human resource development and partnership programs can be a general aim. Supporting these aims was the ultimate goal of creating euroregions and eurometropolises in Western-Europe. The system of euroregions and eurometropolises has been spreading from Western-Europe to the Eastern territories in order that border regions can exploit the comparative advantages being present in border regions even better. The most important aim in border regions, euroregions and eurometropolises is to create an advantageous economic, innovative, academic and social climate by introducing various institutions that can widen the space of successful economy and human resource development, and together with this they can improve the success of regional development planning and human resource development in the border regions of neighboring countries.